Efektivitas Perkuliahan Daring (Online) Pada Mahasisa Menggunakan Aplikasi Zoom Saat Pandemi Covid-19 - Scere Sophia Sitorus; Selviani damayanti Sipayung (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Online lectures are the main means of learning during the Covid-19 pandemic. The Health Information Management Study Program is no exception, which uses online application facilities, such as zoom and online lectures. Zoom meeting is one of the online learning media that is often used by students of Health Information Management Study Program at Stikes Santa Elisabeth Medan. This study aims to analyze the effectiveness of online lectures for students of the Health Information Management Study Program during the Covid-19 Pandemic. Online lectures provide an overview of the lack of optimal understanding of the material and the number of assignments given to students, resulting in an ineffective lecture process. Collecting data in this study using a questionnaire. This research is a quantitative descriptive study using a survey method via an online google form.